2018
DOI: 10.1007/s10930-018-9787-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Theme C Glycoside Hydrolase Family 9 Endo-Beta-Glucanase from a Biogas Reactor Metagenome

Abstract: From a biogas reactor metagenome an ORF (bp_cel9A) encoding a bacterial theme C glycoside hydrolase family 9 (GH9) enzyme was recombinantly produced in E. coli BL21 pQE-80L. BP_Cel9A exhibited ≤ 55% identity to annotated sequences. Subsequently, the enzyme was purified to homogeneity by affinity chromatography. The endo-beta-glucanase BP_Cel9A hydrolyzed the beta-1,3-1,4-linked barley beta-glucan with 24 U/mg at 30 °C and pH 6.0. More than 62% of activity was measured between 10 and 40 °C. Lichenan and xyloglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
1
Order By: Relevance
“…Mg ++ ions inhibited β-1,3–1,4-glucanase activity, similar effect was reported by Celestino et al ( 2006 ), Wang et al ( 2007 ), Apiraksakorn et al ( 2008 ), Yang et al ( 2008 ), Hong et al ( 2009 ), Chaari et al ( 2014 ), Yang et al ( 2014 ) and Elgharbi et al ( 2017 ). This result was dissimilar to the activating effect of Mg ++ ions recorded by Jung et al ( 2010 ), Cheng et al ( 2014 ), Zhang et al ( 2017 ) and Schröder et al ( 2018 ). Partial inhibition of the enzyme occurred by high concentration of Ca ++ , while no change in activity observed with low level, similarly to these data slight inhibition with Ca ++ ions was reported by Apiraksakorn et al ( 2008 ), Elgharbi et al ( 2013 ) and Wang et al ( 2014 ) and dissimilarly Ca ++ ions made activation for other β-1,3–1,4-glucanases (Gao 2016 ; Elgharbi et al 2017 ; Bernardi et al 2018 ).…”
Section: Discussioncontrasting
confidence: 89%
“…Mg ++ ions inhibited β-1,3–1,4-glucanase activity, similar effect was reported by Celestino et al ( 2006 ), Wang et al ( 2007 ), Apiraksakorn et al ( 2008 ), Yang et al ( 2008 ), Hong et al ( 2009 ), Chaari et al ( 2014 ), Yang et al ( 2014 ) and Elgharbi et al ( 2017 ). This result was dissimilar to the activating effect of Mg ++ ions recorded by Jung et al ( 2010 ), Cheng et al ( 2014 ), Zhang et al ( 2017 ) and Schröder et al ( 2018 ). Partial inhibition of the enzyme occurred by high concentration of Ca ++ , while no change in activity observed with low level, similarly to these data slight inhibition with Ca ++ ions was reported by Apiraksakorn et al ( 2008 ), Elgharbi et al ( 2013 ) and Wang et al ( 2014 ) and dissimilarly Ca ++ ions made activation for other β-1,3–1,4-glucanases (Gao 2016 ; Elgharbi et al 2017 ; Bernardi et al 2018 ).…”
Section: Discussioncontrasting
confidence: 89%
“…Research findings have confirmed that metagenomics is a promising approach to tap into the genetic diversity of microbial communities and to discover novel enzymes including several novel glycoside hydrolases belonging to different GH families [53, 54, 55, 22]. A metagenome obtained from Jermuk hot spring served as a source for laminarinase identification.…”
Section: Introductionmentioning
confidence: 97%
“…Chang et al (2016) [24] demonstrated that a cellulase, with endoglucanase activity produced by Geobacillus sp., had binding sites for Ca 2+ and Mg 2+ associated with thermostability of the enzyme, and the addition of these metals assisted to keep high activity values in thermophilic conditions. Similarly, Schröder et al (2018) [25] found and studied an endoglucanase activated by Ca 2+ and Mg 2+ , present in the metagenome derived from a mesophilic biogas plant for biomass treatment. Jeng et al (2019) [26] studied the crystalline structure of an endoglucanase from Clostridium thermocellum, the authors found that the enzyme contained two binding sites for Ca 2+ , which participate in the functionality of the carbohydrate-binding module and the catalytic domain of the enzyme.…”
Section: Introductionmentioning
confidence: 99%